Application of Fermented Starfruit (Asam Sunti) as an Antimicrobial in Keumamah Loin - Aida, Aida; Khairi, Ikhsanul; Akbardiansyah, Akbardiansyah; Fitriani, Fitriani; Rozi, Anhar; Fuadi, Afdhal; Nurhikma, Nurhikma (Fakultas Pertanian Universitas Samudra, 2023)
The purpose of this study was to determine the effect of sunti acid on the ALT and mold as an antimicrobial in keumamah loin. The research is experimental and uses a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment 1 was soaking in sunti acid suspension as much as 10% (F1), as much as 20% (F2), as much as 30% (F3), and without immersion (F0). The parameters observed were ALT and mold. The results of these two studies were analyzed using one way analysis of variance (ANOVA) and continued with Duncan's test. The results showed that the highest ALT was in F0 (7.51x105CFU/mL) and the lowest was in sample F3 (6.36x105CFU/mL), then the highest mold value was in sample F0 (7.68x105CFU/mL), and the lowest was in F3 (6.46x105CFU/mL). The difference in the concentration of sunti acid suspension had a significant effect on the ALT and mold on keumamah loin at the 95% confidence interval